Recent developments and advances in atopic dermatitis and food allergy - Sugita, Kazunari; Akdis, Cezmi A. (Allergology international, 2020)
This review highlights recent advances in atopic dermatitis (AD) and food allergy (FA), particularly on molecular mechanisms and disease endotypes, recent developments in global strategies for the management of patients, pipeline for future treatments, primary and secondary prevention and psychosocial aspects. During the recent years, there has been major advances in personalized/precision medicine linked to better understanding of disease pathophysiology and precision treatment options of AD. A greater understanding of the molecular and cellular mechanisms of AD through substantial progress in epidemiology, genetics, skin immunology and psychological aspects resulted in advancements in the precision management of AD. However, the implementation of precision medicine in the management of AD still requires the validation of reliable biomarkers, which will provide more tailored management, starting from prevention strategies towards targeted therapies for more severe diseases. Cutaneous exposure to food via defective barriers is an important route of sensitization to food allergens. Studies on the role of the skin barrier genes demonstrated their association with the development of IgE-mediated FA, and suggest novel prevention and treatment strategies for type 2 diseases in general because of their link to barrier defects not only in AD and FA, but also in asthma, chronic rhinosinusitis, allergic rhinitis and inflammatory bowel disease. The development of more accurate diagnostic tools, biomarkers for early prediction, and innovative solutions require a better understanding of molecular mechanisms and the pathophysiology of FA. Based on these developments, this review provides an overview of novel developments and advances in AD and FA, which are reported particularly during the last two years. [Display omitted]